ANALISIS GENDER: PERAN GANDA ISTRI PEKERJA BURUH HARIAN DI PERKEBUNAN SAWIT UNTUK MEMENUHI KEBUTUHAN KELUARGA DALAM PERSPEKTIF EKONOMI ISLAM (STUDI DESKRIPTIF PADA PT. LONDON SUMATERA, TRANS SUBUR MUARA LAKITAN, MUSI RAWAS) - Melis Melis (Pusat Studi Gender dan Anak Universitas Islam Negeri Raden fatah palembang, 2018)
The wife's role in the household at this time has shifted out of the house, in the sense that the wife is out of the house to work to help her husband. The phenomenon of women's role and contribution to work is very large can be seen from the spirit of the wives at work. In a gender perspective this is justified. Wives in the village of Trans Subur SP. 2 most of them work as day laborers by